2009
DOI: 10.1258/acb.2009.009066
|View full text |Cite
|
Sign up to set email alerts
|

Determination of fibroblast growth factor 23

Abstract: Background: Fibroblast growth factor 23 (FGF-23) is a recently discovered hormone, which plays a key role in phosphate regulation. To investigate whether FGF-23 can be determined reliably, we validated the three available FGF-23 assays. Methods: Currently, two intact FGF-23 assays (Kainos; Immutopics) and one C-terminal FGF-23 assay (Immutopics) are available. We determined intra-and inter-assay variation, linearity and matrix interference in these assays. Moreover, we compared assay results from healthy subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 8 publications
1
55
0
Order By: Relevance
“…This conclusion is based on the assumption that the C-terminal assay detects cFGF23 and iFGF23, whereas the iFGF23 assay detects only iFGF23 (28). We showed that throughout the day cFGF23 increased, whereas iFGF23 decreased, which suggests accumulation of FGF23 fragments.…”
Section: Discussionmentioning
confidence: 81%
“…This conclusion is based on the assumption that the C-terminal assay detects cFGF23 and iFGF23, whereas the iFGF23 assay detects only iFGF23 (28). We showed that throughout the day cFGF23 increased, whereas iFGF23 decreased, which suggests accumulation of FGF23 fragments.…”
Section: Discussionmentioning
confidence: 81%
“…But studies in which iFGF-23 (kainos; immutopics) and cFGF-23 (immutopics) measurements are compared are inadequate. In a study intra-assay variation was found to be good in all three assays but in terms of interassay and linearity, kainos iFGF-23 and cFGF-23 assays were found to be better 50 . In another study strong positive correlation was determined between iFGF assays and cFGF assay in the HD patients 51 .…”
Section: Discussionmentioning
confidence: 90%
“…The Kainos Intact FGF23 assay is standardized to measure FGF23 in picograms per milliliter; it has a lower limit of detection of 3 pg/ml and intraassay and interassay coefficients of variation of less than 5%. The FGF23 assays were performed using stored plasma or serum according to the specified kit direction (18)(19)(20). All samples were measured in duplicate after a single thaw, with the mean value used in subsequent analysis.…”
Section: Methodsmentioning
confidence: 99%